Market Orientation and Export Performance Study of SMEs in Indonesia with Dynamic Capabilities, Competitive Advantage, and Innovation Capability as Mediating Variables: A conceptual Study - Purmono, Bintoro Bagus; Afifah, Nur; Mustaruddin, Mustaruddin (MultiTech Publisher, 2024)
This conceptual study intends to develop a research framework regarding the impact of market orientation on the export performance of small and medium enterprises (SMEs) in Indonesia, by considering the mediating role of dynamic capabilities, competitive advantage, and innovation capabilities. It is hoped that this conceptual study will contribute to analyzing the complex relationships between existing variables to provide insight into how Indonesian SMEs can increase their competitiveness in international markets. This research can be developed quantitatively, utilizing structural equation modeling to test the proposed conceptual framework. The development results of this research can have valuable implications for SME managers and policymakers who seek to increase the export success of Indonesian companies in an increasingly globalized business environment.